Florida Keys Cassiopea host benthos-like external microbiomes and a gut dominated by Vibrio, Endozoicomonas and Mycoplasma - Kaden M. Muffett; Jessica M. Labonté; Maria Pia Miglietta (PLoS ONE, 2025)
Interactions with microbial communities fundamentally shape metazoans’ physiology, development, and health across marine ecosystems. This is especially true in zooxanthellate (symbiotic algae-containing) cnidarians. In photosymbiotic anthozoans (e.g., shallow water anemones and corals), the key members of the associated microbiota are increasingly well studied, however there is limited data on photosymbiotic scyphozoans (true jellyfish). Using 16S rRNA barcoding, we sampled the internal and external mucus of the zooxanthellate Upside-Down Jellyfish, Cassiopea xamachana during August throughout eight sites covering the full length of the Florida Keys. We find that across sites, these medusae have low-diversity internal microbiomes distinct from the communities of their external surfaces and their environment. These internal communities are dominated by only three taxa: Endozoicomonas cf. atrinae, an uncultured novel Mycoplasma, and Vibrio cf. coralliilyticus. In addition, we find that Cassiopea bell mucosal samples were high diversity and conform largely to the communities of surrounding sediment with the addition of Endozoicomonas cf. atrinae. The microbial taxa we identify associated with wild Florida Keys Cassiopea bear a strong resemblance to those found within photosymbiotic anthozoans, increasing the known links in ecological position between these groups.